1994
DOI: 10.1210/jcem.79.4.7962289
|View full text |Cite
|
Sign up to set email alerts
|

Hypersecretion of androstenedione by isolated thecal cells from polycystic ovaries.

Abstract: The aim of this study was to examine the hypothesis that hypersecretion of ovarian androgens in polycystic ovary syndrome results from an intrinsic abnormality of androgen biosynthesis by thecal cells. Steroid accumulation by human thecal cells from normal and polycystic ovaries (PCO-theca) was examined under basal and LH-stimulated conditions. A method for dispersing and culturing human thecal cells as primary monolayers in serum-free medium was developed. LH increased androstenedione (A), progesterone (P), 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
111
0
12

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(129 citation statements)
references
References 1 publication
6
111
0
12
Order By: Relevance
“…It is not too difficult to identify biochemical pathways that may be disrupted in PCOS. There is evidence for an intrinsic disorder of ovarian folliculogenesis, [45][46][47] constitutive hypersecretion of androgens by theca cells 48,49 and disordered secretion and action of insulin 50 (Figure 1). There are, however, obvious problems in searching for candidate genes in PCOS: the heterogeneous nature of the syndrome has given rise disagreement about definition and diagnostic criteria; in addition expression of features of PCOS occurs predominantly in women of reproductive age and there is no clear male phenotypeFboth of which make family-based studies difficult.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not too difficult to identify biochemical pathways that may be disrupted in PCOS. There is evidence for an intrinsic disorder of ovarian folliculogenesis, [45][46][47] constitutive hypersecretion of androgens by theca cells 48,49 and disordered secretion and action of insulin 50 (Figure 1). There are, however, obvious problems in searching for candidate genes in PCOS: the heterogeneous nature of the syndrome has given rise disagreement about definition and diagnostic criteria; in addition expression of features of PCOS occurs predominantly in women of reproductive age and there is no clear male phenotypeFboth of which make family-based studies difficult.…”
Section: Introductionmentioning
confidence: 99%
“…The studies from our own laboratory provide a cautionary tale in the saga of the quest for candidate genes. On the basis of the evidence for a primary abnormality in theca cells steroidogenesis, 48,49 we investigated a polymorphism (a pentanucleotide repeat sequence) in the promoter of CYP11A (coding for P450 cholesterol sidechain cleavage, the rate-limiting enzyme at the origin of the steroidogenic pathway) in a relatively small case-control series and a family-based study. We found evidence for linkage and association with PCOS and testosterone levels at the CYP11A locus.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on freshly isolated thecal tissue or cultures of theca cells derived from normal and PCOS women have demonstrated that PCOS theca secretes greater amounts of androgen than theca tissue or cells from regularly ovulating women (12,(14)(15)(16)(17)(18)(19). Increased androgen biosynthesis in PCOS theca cells results from increased expression of the key enzymes involved in androgen biosynthesis, steroid-17-α-hydroxylase/17,20 lyase (encoded by the CYP17A1 gene) and cholesterol side-chain cleavage enzyme, mitochondrial (encoded by the CYP11A1 gene) (15)(16)(17)20).…”
mentioning
confidence: 99%
“…Polycystic ovaries appear to occur as a dominant trait, with a suggestion of a counterpart male phenotype of premature male-pattern baldness [44,45]. Polycystic ovaries from asymptomatic women have an abnormal steroidogenic pattern similar to that of women with PCOS in vitro [46], and ovarian function testing shows them to have a subclinical increase in androgens [47][48][49].…”
Section: Etiology Of Polycystic Ovary Syndromementioning
confidence: 99%